Three-Dimensional Calvarial Growth in Spring-Assisted Cranioplasty for Correction of Sagittal Synostosis. Issue 7 (October 2020) - Rodriguez-Florez, Naiara; Borghi, Alessandro; Yauwan, Daniel D.; Heuntinck, Pam; Bruse, Jan L.; Tenhagen, Maik; Göktekin, Özge K.; Angullia, Freida; Schievano, Silvia; Dunaway, David J.; Jeelani, Noor Ul Owase; James, Greg
Abstract : Abstract: Spring-assisted cranioplasty (SAC) is a minimally invasive technique for treating sagittal synostosis in young infants. Yet, follow-up data on cranial growth in patients who have undergone SAC are lacking. This project aimed to understand how the cranial shape develops during the postoperative period, from spring insertion to removal. 3D head scans of 30 consecutive infants undergoing SAC for sagittal synostosis were acquired using a handheld scanner pre-operatively, immediately postoperatively, at follow-up and at spring removal; 3D scans of 41 age-matched control subjects were also acquired. Measurements of head length, width, height, circumference, and volume were taken for all subjects; cephalic index (CI) was calculated. Statistical shape modeling was used to compute 3D average head models of sagittal patients at the different time points. SAC was performed at a mean age of 5.2 months (range 3.3–8.0) and springs were removed 4.3 months later. CI increased significantly ( P  < 0.001) from pre-op (69.5% ± 2.8%) to spring removal (74.4% ± 3.9%), mainly due to the widening of head width, which became as wide as for age-matched controls; however, the CI of controls was not reached (82.3% ± 6.8%). The springs did not constrain volume changes and allowed for natural growth. Population mean shapes showed that the bony prominences seen at the sites of spring engagement settle over time, and that springs affect the overall 3D head shape of the skull. In conclusion, results reaffirmed the effectiveness of SAC as a treatment method for nonsyndromic single suture sagittal synostosis. Abstract : Supplemental Digital Content is available in the text